Periodic Solutions for a System of Difference Equations - Shugui Kang; Bao Shi (Discrete Dynamics in Nature and Society)
This paper deals with the second-order nonlinear systems of difference equations, we obtain the existence theorems of periodic solutions. The theorems are proved by using critical point theory.